Coming Back to Physiology: Extra Hepatic Functions of Proprotein Convertase Subtilisin/Kexin Type 9 - Schlüter, Klaus-Dieter; Wolf, Annemarie; Schreckenberg, Rolf (Frontiers in Physiology, 2020)
Neuronal apoptosis regulated convertase-1 (NARC-1), nowadays mostly named proprotein convertase subtilisin/kexin type 9 (PCSK9), has got a lot of attention due to the fact that it is a key regulator of the low-density lipoprotein (LDL)-receptor and therefore involved in hepatic LDL-clearance. Within a few years therapies targeting PCSK9 have reached the clinical practice and they offer an additional tool to reduce blood cholesterol concentrations. However, PCSK9 is nearly ubiquitously expressed in the body but has less well understood functions and target proteins in extra hepatic tissues. As such, PCSK9 is involved in the regulation of neuronal survival and protein degradation, it affects the expression of the epithelial sodium channel (ENaC) in the kidney, it interacts with white blood cells and with cells of the vascular wall, it modifies contractile activity of cardiomyocytes, and contributes to the regulation of cholesterol uptake in the intestine. Moreover, under stress conditions, signals from kidney and heart can affect the hepatic expression and thereby the plasma concentration of PCSK9 which than in turn can affect other target organs. Therefore, there is an intense relationship between local (autocrine) and systemic (endocrine) effects of PCSK9. Although, PCSK9 has been recognized as a ubiquitously expressed modifier of cellular function and signaling molecules, its physiological role in the different organs is not well understood. The current review summarizes these findings.